A review of the cicada genus Mata Distant, 1906 (Hemiptera: Cicadidae) with description of one new species from China - Wang, Siyue; Jiang, Jinyuan; Wei, Cong (Zootaxa, 2024)
The cicada genus Mata Distant, 1906 was reviewed based on the description of one new species, Mata uncinulata sp. nov., from China. Mata kama (Distant, 1881) and Mata meghalayana Sarkar, Mahapatra, Mohapatra, Nair & Kunte, 2021 are reported for the first time in China. Morphological phylogenetic analysis reveals the relationships among related species of Mata. Partial mitochondrial COI gene (DNA barcoding) of M. uncinulata sp. nov. and M. kama rec. nov. are sequenced and uploaded to GenBank. A key to species of Mata is provided.